Empirical evidence of frequency of change and job burnout - R. Mat Zin; A. Nehari Talet (South African Journal of Business Management, 2016)
This study focused on two main constructs; frequency of change (FoC) and the job burnout in the workplace. It employed a quantitative design to examine the relationship between employees' perceived "frequency of change" (FoC) occurring intheir organizations and job burnout subscales – exhaustion, cynicism and professional efficacy. The respondents were low and middle level staff; managers and senior managers in selected manufacturing, information technology (IT) serviceorganizations. Significant differences were found in levels of exhaustion between Financial Services employees and employees of other organization types. Finally, the difference was shown to exist in levels of cynicism between senior managers and employees when perceived FoC is high.
Keywords: 650